Plurality and diversity of family relations in Europe / edited by Katharina Boele-Woelki, Dieter Martiny. - Boele-Woelki, Katharina; Martiny, Dieter (European family law series., 2019)
This volume contains the contributions delivered at CEFL's sixth international conference, which focused on comparative and international family law in Europe in their respective cultural contexts. Inter alia in this book CEFL experts and other legal scholars address the CEFL and its Principles, the interrelation of family law and family sociology, family migration, children's and women's fundamental rights, as well as the developing concept of parenthood, the role of children in family proceedings, extra-judicial divorces and ADR in family matters. While the development of modern trends in European family law is going on, some new challenges arise and old challenges remain. The awareness of more plurality and diversity in family relationships is increasing. Both pose problems. New legal solutions have to be integrated into the existing family law system. On the other hand, there are tensions between modern fundamental values and traditional religious solutions. For both a deeper analysis is necessary. The conference, and in turn the book, aims to enhance the exchange of ideas and arguments on comparative and international family law in Europe.